Analisis Kemampuan Kognitif Peserta Didik Melalui Model Pembelajaran Problem Based Learning - Inna, Suriani; Karlina, Asta (Biocaster : Jurnal Kajian Biologi, 2021)
This study aims to obtain information about the use of Problem Based Learning model to increase students' cognitive abilities. The research method used is a quasi-experimental One Group Pretest-Posttest Design, with the research subjects of 31 students of class X at SMA Citra Bangsa Makassar. Students are divided into three categories of ability groups, namely: high, medium and low based on the average value of daily tests. The instruments used were multiple choice written tests, essays, observation sheets, and interview guide questionnaires. The increase in learning outcomes is calculated using the gain normalization formula and the average N-Gain relationship test. The results showed that this learning model showed a significant increase in student learning outcomes with an average N-gain percentage of 65.33% for all students. The highest increase in learning outcomes was achieved by students in the high category (N-gain = 68%). The students gave positive responses to learning, and they felt happy and motivated in participating in learning using the implemented learning model.